Sistem Pendukung Keputusan Penerimaan Raskin Desa Mabung Kabupaten Nganjuk Menerapkan Metode Simple Additive Weighting (SAW) - Efendi, Fery Sofian (Jurnal Informatika dan Multimedia, 2016)
Raskin is subsidized food intended for low income households. In determining the recipient of raskin mabung village there are still problems such as the distribution of rice is isplaced. Decision support system will ease the public and officers in determining acceptance raskin. These issues can be helped by the decision support system acceptance raskin mabung village nganjuk apply simple additive weighting method. Simple additive weighting method is finding a weighted summation of the performance rating for each alternative on all atributes. Simple additive weighting method is weighted in determining whether a decision lies in the ability to perform more precise asessment because it is based on the value of the preference criteria and weighting that have been determined. Decision support system acceptance raskin mabung village was created using a web programming language with supporters using mysql database. On decision support system acceptance raskin maung village there is a system that can process data on population, the candidate receiving the data, the data submission, and complaint data and present the data recipients raskin mabung village in report form. To study continue decision support system can be corrected at the design of the display and graph the number of recipients raskin, raskin filing and complaints or the addition of other features